Characterizing the evolution of detached limestone blocks on hillslopes: Konza Prairie, Kansas, United States of America - Stumpff, Michael L (Kansas State University, 2021)
The landscapes we live in are dynamic. If we want to increase our understanding of the mechanisms at play and enhance our confidence when making landscape management decisions, then we must deduce what processes are most significant in landform formation, and what their rates are. The need for understanding is particularly strong in landscapes that remain in their natural state, for instance landscapes with soft bedrock or those incompletely covered by vegetation such as the Flint Hills in Kansas. In such locations, layers of harder lithologies, even when thin, are key controls on landscape formation. This is because blocks that detach from harder layers, armor soil downslope against erosion and create obstacles behind which eroding soil can accumulate. However, it is not known how properties of such detached blocks change during their stay on the hillslope, or which factors affect such changes. My objective in this study was thus to understand the mechanisms of production, transport and rates of change of blocks on hillslopes, specifically of Detached Limestone Blocks (DLBs) in the Flint Hills KS, USA. I used field measurements and Structure from Motion photogrammetry to quantify DLB position and properties on slopes under hard limestone layers. Observations from the sites suggested DLBs decrease in size with distance downslope, DLBs hardness values do not change significantly while being transported downslope, DLBs in either vegetation type harden at similar rates and have block oreintations similar with the residing hillslope, and lastly, that slope steepness has an influence on DLB relative slopes, potentially highlighting different transport methods taking place in steeper hillslopes.
Keywords: Konza Prairie; Hillslopes; Geomorphology